Instrumentation of rainbow refractometry: portable design and performance testing. (12th June 2018) - Wu, Xue-cheng; Li, Can; Cao, Kai-lin; Cao, Jian-zheng; Wu, Ying-chun; Chen, Ling-hong; Gao, Xiang; Gréhan, Gérard; Cen, Ke-fa
Abstract: Accurate measurement of various key parameters is indispensable for the characterization of spray droplets. Global rainbow refractometry shows great potential for its unique capability of measuring the refractive index (RI) of a droplet, but is still restricted to the laboratory. A portable design of a global rainbow refractometry instrument is implemented based on a new optical layout, with software developed as well. This instrument has four operation modes in its hardware design. Performance testing on the instrument consists of image quality, multi-working distance measurement, and measurement accuracy. The quality of the rainbow image is improved using the new system. The results of the multi-working distance measurement show that the measured refractive indices with working distances of 16, 25, and 30 cm are exact with a maximum deviation of about 2 × 10 −4, while the deviation is as large as 1.2 × 10 −3 at 50 cm, which is explained by the aberration from a long working distance (⩽32–35 cm). The measurement accuracy is verified further by ethanol–water spray droplets with volume concentrations of 0%–100%. The mean error of the RI measurement is about 2 × 10 −4 at different concentrations. The measured mean droplet diameter has an accuracy of 2 µ m in the experiments. The rainbow refractometry instrument has great potential for in situ measurement of various sprays, i.e. spray combustion/pollutant removal in a large containment.